Part I: consensus statements and expert recommendations for HER2-negative early breast cancer in the Asia-Pacific region: diagnosis and risk assessment - Lee, Soo Chin; Park, Yeon Hee; Singer, Christian F.; Balmaña, Judith; Dent, Rebecca Alexandra; Tan, Veronique Kiak-Mien; Mulansari, Nadia Ayu; Yusof, Mastura Md; Que, Frances Victoria F.; Lu, Yen-Shen; Parinyanitikul, Napa; Pham, Cam Phuong; et al. (Frontiers in Oncology, 2025)
IntroductionIn the Asia-Pacific region, there is increasing contention on the practical challenges involved in managing human epidermal growth factor receptor 2 (HER2)-negative early breast cancer (eBC). This modified Delphi consensus explores gaps in genetic counselling (GC) and genetic testing (GT), and clinical risk assessment for HER2-negative eBC.MethodsAn expert panel of 16 Asia-Pacific medical oncologists, geneticists, and breast cancer surgeons arrived at 33 statements. The level of statement consensus was considered high at ≥75%. A survey of 134 healthcare practitioners (HCPs) (breast cancer surgeons, geneticists, oncologists, molecular biologists/pathologists) explored the real-world practices in this region.ResultsA consensus was reached for 88% of the statements (29/33) and aligned with international guidelines. Experts reached 100% consensus on offering pretest GC, obtaining consent before GT, considering first diagnosis of breast cancer (BC) as ideal time for GT, offering reflex testing for patients with likely/pathogenic germline BRCA variant, and considering patients with germline BRCA mutant early triple-negative breast cancer (TNBC) patients who do not achieve pathological complete response after neoadjuvant treatment to be at high risk of recurrence. Over 90% of experts supported germline GT for BRCA for TNBC patients irrespective of age at diagnosis or family history and prioritised tumour size and nodal status as prognostic factors for cancer recurrence. Experts reached 80%-90% consensus for using genetic risk assessment tools in low/under-resourced healthcare systems and considering patients with likely/pathogenic variants in BRCA for risk reduction surgery. Significant gaps existed between real-world practices and recommendations, particularly in offering pretest GC to patients with suspected hereditary BC and to blood relatives of patients with BRCA germline pathogenic variant BC, ideal time for GT, considering GT for early TNBC patients irrespective of age, offering post-test GC for positive results, utilising risk assessment tools, and streamlining GC through non-geneticist HCPs.ConclusionGT and pretest GC should be mainstreamed at the first diagnosis of BC. Risk assessment for disease recurrence should be performed at diagnosis and post-surgery for HER2-negative eBC patients. These recommendations would help standardise GC and improve GT access for clinical decisions.